The Role of Integrated Reporting in Income Smoothing, Tax Avoidance, Idiosyncratic Risk – Case of Manufacturing Sector - Much. Rizal P. Geno; Amrie Firmansyah; Dani Kharismawan Prakosa (Accounting Analysis Journal, 2022)
Purpose : Idiosyncratic risk directly affects investment. The failure to foresee the risk may cause investors to suffer an enormous capital loss. Thus, this study investigates the effect of corporate policies, i.e., income smoothing and tax avoidance, on idiosyncratic risk. The use of integrated reporting as moderating variable is essential in these associations. Method : The analysis includes 90 manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2020, obtaining a total sample of 450 firm-year. Multiple linear regression models for panel data are employed to test the hypotheses. Findings : Our findings suggest that tax avoidance positively correlates with idiosyncratic risk, while integrated reporting strengthens these relationships. In contrast, income smoothing is not associated with idiosyncratic risk. However, the interaction between income smoothing and integrated reporting is negatively associated with idiosyncratic risk. Our finding proves that idiosyncratic risk can be costly due to porous corporate policies. It bridges investors understanding of idiosyncratic risk and improves their foresight, allowing them to anticipate managers’ transgression. A better understanding of idiosyncratic risk may also help local tax authorities to improve compliance risk management for taxation purposes. This study demonstrates that market regulators may benefit from enhanced integrated reporting implementation by listed companies. Novelty : This study includes integrated reporting, which encourages companies to be more transparent in providing information to the public, as a moderating variable in testing the effect of income smoothing and tax avoidance on idiosyncratic risk, which are rarely used in previous references. Keywords : Idiosyncratic Risk; Income Smoothing; Tax Avoidance; Integrated Reporting; Manufacturing Company